Preparation and characterization of silver nanoparticles using surian (Toona sinensis) leaf extract and the wound healing efficacy in mice - Dini Hanifa; Armenia Armenia; Akmal Djamaan (Nanomedicine Journal, 2024)
Objective(s): Green synthesis is a method of forming silver nanoparticles (AgNP) that is widely developed because it uses natural reducing agents, which are safer and more environmentally friendly. This study investigates the formation of silver nanoparticles using surian (Toona sinensis (Juss.) M. Roem) leaf extract as a bioreductor and its wound healing effectivity in mice. Materials and Methods: T. sinensis leaf was extracted by distilled water in 1:10 ratio at 90 °C for 15 min using magnetic stirrer. 0.5 mL of 0.1 M AgNO3 was mixed with 0.25 mL of 10% T. sinensis leaf extract, diluted to 50 mL, and stirred for 4 hr. The UV-Vis spectrum was measured at 300-800 nm. Particle size, morphology, functional group, and crystal structure of silver nanoparticles were characterized. For wound healing properties, mice were divided into seven groups, and each group experienced wounds induced by HCl on their dorsal side, followed by various treatments. Wound healing was monitored over 18 days, and statistical analysis assessed the effect of silver nanoparticle concentration and treatment duration.Results: The formation of colloidal silver nanoparticles was indicated by a change in the color from colorless to brown. The silver nanoparticles had the Surface Plasmon Resonance (SPR) band at 420 nm, spherical with an average size of 39 nm, and crystalline with a face-centered cubic structure. These silver nanoparticles could accelerate wound healing in mice compared to the negative control group, the group given silver sulfadiazine, AgNO3, and T. sinensis leaf extract alone (P<0.05). Conclusion: This shows that silver nanoparticles mediated by T. sinensis leaf extract have the potential to be developed into wound healing agents.